STUDI NORMATIF YURIDIS SENGKETA PENYALAH GUNAAN HARTA GONO GINI - Ubaidillah, M. Burhanuddin; Shinwanuddin, M. (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2023)
In practice, disputes often arise between married couples in the division of marital property in court. Even in the court process, there are often disputes about the division of marital property, which further complicates the divorce process because each party claims that the property is part of their rights. This article focuses on a normative juridical study of disputes over the misuse of marital property due to death, divorce, and polygamy. It begins by examining the concept of normative juridical methods, the historical roots of the term